Therapeutic Nanoparticles for the Different Phases of Ischemic Stroke - Bernardo-Castro, S (2021)
Stroke represents the second leading cause of mortality and morbidity worldwide. Ischemic strokes are the most prevalent type of stroke, and they are characterized by a series of pathological events prompted by an arterial occlusion that leads to a heterogeneous pathophysiological response through different hemodynamic phases, namely the hyperacute, acute, subacute, and chronic phases. Stroke treatment is highly reliant on recanalization therapies, which are limited to only a subset of patients due to their narrow therapeutic window; hence, there is a huge need for new stroke treatments. Nonetheless, the vast majority of promising treatments are not effective in the clinical setting due to their inability to cross the blood-brain barrier and reach the brain. In this context, nanotechnology-based approaches such as nanoparticle drug delivery emerge as the most promising option. In this review, we will discuss the current status of nanotechnology in the setting of stroke, focusing on the diverse available nanoparticle approaches targeted to the different pathological and physiological repair mechanisms involved in each of the stroke phases.